The Impact of Insurer Financial Health and Market Discipline on Life Insurance Demand: A Case Study of Indonesia - Kristio Rapi; Dominicus Savio Priyarsono; Siti Jahroh; Toni Bakhtiar (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The life insurance industry in Indonesia has faced "crisis" involving negative profits, bankruptcies, and insolvencies in insurance companies that cost the people and the country more than IDR 16 trillion, along with a decrease in life insurance penetration over the last decade, from 1.28% in 2018 to 0.98% in 2022. The decrease even occurs when government support has increased and consumers experience the positive contributions of life insurance. The unhealthy industry is arguably causing the decrease in life insurance demand in Indonesia, but current studies on life insurance demand often focus on the consumer's side. Meanwhile, studies on a company's financial soundness and its impact on consumers' decisions to purchase life insurance are still lacking.Purpose: The purpose of this study is to analyze the effect of insurers' financial health on life insurance purchases in Indonesia and the existence of market discipline in the life insurance industry in IndonesiaDesign/methodology/approach: This study analyzes the effect of insurers' financial health, based on POJK number 71/POJK.05/2016, and consumer responses through market discipline on life insurance demand in Indonesia, using data from twenty-five selected life insurance companies from 2007 to 2022. We uses Generalized Method of Moment (GMM) to estimate panel data.Findings/Result: This study finds that financial health of insurance company has significantly affect consumers purchase on life insurance and consumers implementing market discipline. Solvency is the best predictor of life insurance demand, as an increase of indicator raises the number of policies, while a decrease of indicator in precendence year prompts consumers to respond by decreasing the premium. Consumers also implement market discipline regarding reserves and equity, as a decrease in both factors in the prior year has a significant negative effect on premium per policy and premium.Conclusion: Unhealthy finances of insurance companies have contributed to low life insurance purchases in Indonesia. Therefore, significant efforts to improve financial soundness in life insurance companies in Indonesia should be supported, such as the improvement of investment management and the enhancement of capital equity adequacy through business consolidation. Regulators should also support market discipline by issuing regulations to improve data transparency and in supervising market conduct and micro prudential aspects of companies, while companies have role in clarifying insurance policies and information that is disseminated through their marketing teams.Originality/value (State of the art): This study is the first to examine the effect of financial health of insurers, using indicators from POJK number 71/POJK.05/2016, on consumers’ decisions in purchasing life insurance. This study is also the first to show evidence of market discipline behavior in life insurance industry in Indonesia. Keywords:  corporate finance, financial health, life insurance demand, market discipline, insurance company